Statistics for research with a guide to SPSS - Argyrous, George 1963- (SAGE, 2011)
The clearest and most straightforward explanations of statistical concepts are combined with lots of practical examples from a variety of disciplines, now with a brand new website with additional resources for students and lecturers.